Integrated Techno-Economic Evaluation, Monte Carlo Probabilistic Reliability, Unit Commitment Optimization, and Frequency Stability of Small Modular Reactor (SMR) Integration in Isolated Systems of 300–1000 MW - Gunawan T. Hadiyanto; Intan Kumala Sari (Journal of Engineering, Electrical and Informatics, 2026)
Electric power systems in island regions often operate as isolated grids, heavily dependent on diesel generators, leading to high fuel costs and vulnerability to fluctuations in global energy prices. This study presents an integrated evaluation framework for analyzing the integration of Small Modular Reactors (SMRs) into these isolated power systems. The research combines techno-economic analysis using Levelized Cost of Electricity (LCOE), probabilistic reliability simulation through Sequential Monte Carlo Simulation, operational optimization with the Unit Commitment model, and system frequency stability analysis. A case study was conducted on an island grid system with a peak load of 650 MW. The simulation results show that integrating SMRs can reduce Expected Energy Not Served (EENS) by over 60% and yield a median LCOE of approximately 77 USD/MWh. These results suggest that SMRs offer a reliable, cost-effective generation solution for isolated grids, improving both energy security and economic efficiency by reducing reliance on diesel and enhancing the sustainability of energy systems in remote areas.